Synthesis and biological evaluation of Schizandrin derivatives as tubulin polymerization inhibitors. Issue 16 (15th August 2020) - Dileep Kumar, G.; Siva, B.; Bharathi, K.; Devi, A.; Pavan Kumar, P.; Anusha, K.; Lambhate, Surbhi; Karunakar, T.; Kumar Tiwari, Ashok; Suresh Babu, K.
Graphical abstract: Abstract: A series of oxime ester-derivatives were prepared by utilizing the schizandrin (1 ), a major compound isolated from Schisandra grandiflora, which is deployed in different traditional system of medicine. The in vitro antiproliferative activities of the synthesized compounds were assessed against a selected panel of human cancer cell lines (A549, RKO P3, DU145 and Hela) and normal cell (HEK293). Several of these derivatives were found more potent in comparison to parent compound, schizandrin (1 ). Particularly, 4a and 4b demonstrated potent activity against DU-145 and RKOP3 cell lines with IC50 values of 3.42 µM and 3.35 µM respectively. To characterize the molecular mechanisms involved in antitumoral activity, these two compounds, 4a and 4b were selected for further studies. Cell cycle analysis revealed that both the compounds were able to induce apoptosis and cell cycle arrest at G0 /G1 phase. To know the extent of apoptosis in DU145 and RKOP3 cell lines, Annexin V-FITC were performed. Moreover, the tubulin polymerization assay indicated that 4a and 4b exhibits potent inhibitory effect on the tubulin assembly. Molecular docking studies and competitive binding assay also indicated that 4a and 4b effectively bind at the colchicine binding site of the tubulin.